ICEBEAR‐3D: A Low Elevation Imaging Radar Using a Non‐Uniform Coplanar Receiver Array for E Region Observations. Issue 3 (25th February 2022) - Lozinsky, Adam; Hussey, Glenn; McWilliams, Kathryn; Huyghebaert, Devin; Galeschuk, Draven
Abstract: The Ionospheric Continuous‐wave E region Bistatic Experimental Auroral Radar (ICEBEAR) has been reconfigured using a phase error minimization and stochastic antenna location perturbation technique. The resulting 45‐baseline sparse non‐uniform coplanar T‐shaped array, ICEBEAR‐3D, is used for aperture synthesis radar imaging of low elevation targets. The reconfigured receiver antenna array now has a field of view ±45° azimuth and 0°–45° elevation at 0.1° angular resolution. Within this field of view no aliasing occurs. Radar targets are imaged using the Suppressed Spherical Wave Harmonic Transform (Suppressed‐SWHT) technique. This imaging method uses precalculated constant coefficient matrices to solve the integral transform from visibility to brightness through direct matrix multiplication. The method then suppresses image artefacts (dirty beam) due to undersampling by combining brightness maps of differing harmonic order. Measuring elevation angles of targets at low elevations with radar interferometers has been a long standing problem. ICEBEAR‐3D elucidates the underlying misinterpretations of the conventional geometry for vertical interferometry especially for low elevation angles. The proper phase reference vertical interferometry geometry is given which allows radar interferometers to unambiguously measure elevation angles from zenith to horizon without special calibration. The receiver antenna array reconfiguration, Suppressed‐SWHT imaging technique, and proper geometry for vertical interferometry are validated by showing agreement of the meteor trail altitude distribution with numerous data sets from other radars. Key Points: Ionospheric Continuous‐wave E region Bistatic Experimental Auroral Radar receiver antenna array reconfiguration design based on a phase error minimization technique Aperture synthesis imaging using the Suppressed Spherical Wave Harmonic Transform (Suppressed‐SHWT) Application of the proper geometry for vertical interferometry resolves low elevation angles unambiguously